The Effect of Nutrition Counseling on Protein Intake on Patients with Chronic Kidney Failure who Undergo Hemodialization in Cut Mutia Hospital, Aceh Utara - Desriyani Desriyani; Yulia Fitri; Silvia Wagustina; Nunung Sri Mulyani (Jurusan Gizi, Poltekkes Kemenkes Aceh, 2021)
Patients with kidney failure in outpatient hemodialysis rooms often experience malnutrition and have decreased quality of life. Moroever, they frequently have incorrect knowledge about nutritional intake, especially protein. One way to deal with nutritional problems in kidney patients in outpatient hemodialysis rooms is nutrition counseling to provide knowledge about food handling/control. This counseling aims to enable patients to change their nutritional intake, especially protein. Thus, their nutritional and health status gets better and improved. This study aims to determine the effect of nutritional counseling on protein intake in patients with chronic kidney failure at the Cut Mutia Hospital, Aceh Utara. This research employed a descriptive-analytical method with a quasi-experimental design and a one-group pretest-posttest design. The research sample was 28 chronic kidney failure patients in outpatient hemodialysis rooms at RSUD Cut Mutia Aceh Utara. They were divided into two groups: 14 patients in a treatment group and 14 patients in a control group. The patients received nutrition counseling for 30 minutes in the pre-test and post-test. The data were analyzed using a statistical test of the dependent T-test. The average protein intake in the treatment group before and after the nutritional counseling is 40.60 grams, and the average protein intake after the control group is 52.91 grams. The nutritional counseling significantly affects the protein intake of patients with chronic kidney failure in outpatient hemodialysis rooms at Cut Mutia Hospital, Aceh Utara (p = 0.00).